Inner grace Augustine in the traditions of Plato and Paul - Cary, Phillip, 1958- (Oxford ; New York : Oxford University Press, 2008)
Most theologians want to paint the development of Augustine's doctrine of grace as a turn away from Platonist philosophy to something more distinctively Christian, but Phillip Cary argues that it is a synthesis of the two, a development within Augustine's Christian Platonism.
Platonist grace : inner help to love -- Wisdom and virtue -- Conversion and purification -- Beauty and love -- Free will against autonomy -- From fear to love -- Against Augustine on the Jews -- Dialogue with Plato -- The widening scope of inner help -- Connections of love -- Pauline grace : human will and divine choice -- Good will before Paul -- Willing becomes difficult -- Stages -- The place of merit -- Early inconsistency -- Jacob and Esau -- The call to faith -- Assent or delight? -- No external cause of grace -- Reading Paul's admonition -- Anti-pelagian grace : clarifying prevenience -- The shape of the controversy -- The grace of participation -- Uncovering pelagian evasions -- Augustine's evasiveness -- The missing piece of the puzzle -- Taught by God -- Predestined grace : conversion and election -- The grace of beginnings -- Converting Paul's will -- Coercion on the Damascus Road -- The experience of grace in disarray -- God turns hearts -- Problems of perseverance -- Biblical election.
Includes bibliographical references and index.
Keywords: Augustine, -- Saint, Bishop of Hippo; Bible. -- Theology; Grace (Theology); RELIGION -- Christianity -- General; RELIGION -- Christian Theology -- Systematic; Electronic books